1984
DOI: 10.1007/bf01951980
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase binds to collagen; a hypothesis on the mechanism of extravesicular mineralization in epiphyseal cartilage

Abstract: Affinity chromatography on Sepharose 4B-collagen gels was used to test the affinity of alkaline phosphatase for collagen. Results indicate that alkaline phosphatase of preosseous cartilage binds to collagen probably by electrostatic interactions, this interaction is inhibited by proteoglycan subunits. These results suggest that, in vivo, the formation of a collagen-alkaline phosphatase complex may be a step of the process leading to cartilage calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…Initial experiments using affinity chromatography, identified collagen type I, II, and X as binding partners of TNAP [573][574][575]. The interaction of collagens with TNAP is thought to be important as a nucleator for the process of skeletal calcification.…”
Section: Protein Interactionsmentioning
confidence: 99%
“…Initial experiments using affinity chromatography, identified collagen type I, II, and X as binding partners of TNAP [573][574][575]. The interaction of collagens with TNAP is thought to be important as a nucleator for the process of skeletal calcification.…”
Section: Protein Interactionsmentioning
confidence: 99%
“…The mechanism by which MV-initiated HA crystals transfer to collagen fibers remains elusive. However, some previous results suggest the formation of a collagen-ALP complex as a step in the process initiating the deposit of crystalline HA in and around collagen fibrils [63,64] (Fig. 3).…”
Section: Mineralization Of Bone Matrixmentioning
confidence: 89%
“…Prior studies have mainly reported binding of various ALP isozymes to collagen type II [58,63,64,102]. In paper III, we investigated the binding properties of human BALP to human collagen type I, the major structural component in the extracellular matrix of bone.…”
Section: Paper IIImentioning
confidence: 99%
“…Chicken TNAP is known to bind collagen I, 11, and X (Vittur et al, 1984;Wu et al, 19911, a property which has been attributed in part to a flexible surface loop in the region between K405 and V442 of mTNAP (Bossi et al, 1993). Although the mammalian enzymes are almost identical in this region, chTNAP shows only 76.4% conservation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its enzymatic activity, it has been suggested that AP might function as a structural cell surface molecule capable of directing cell migration and adhesion in development Steinberg, 1988, 1989). In support of a structural role for AP is the demonstration that AP can bind to collagen (Vittur et al, 1984;Wu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%